Konseling Individu Pendekatan Rational Emotive Therapy dalam Menumbuhkan Minat Siswa Melanjutkan Studi ke Perguruan Tinggi - Prilisa, Prilisa; AS, Enjang; Effendi, Dudy Imanuddin (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2024)
This study aims to determine how the Activating Experience (A), Belief System (B), and Emotional Consequence (C) in class XII MA Pondok Quran Boarding School students and find out Disputing (D) and Effect Emotional Consequence (E) on students after the individual counseling process with the RET approach. The research method used is a case study with a qualitative approach. The results showed: (A) the students were personal events, family events, and students' environmental events. (A) affect (B) ie college is not important for businessmen and entering college is not easy. This has an effect on (C), namely, self-awareness, self-management, social awareness, and student relationship management. Then the counseling guidance teacher performs (D) by giving questions and statements that lead to student awareness, giving students an understanding of the importance of lectures, and ensuring students understand what the counseling guidance teacher gives. Then, (E) on students, namely students can think rationally and the growth of student interest in lectures.